Method validation for determination of released cadmium, chromium, lead, molybdenum and nickel from stainless steel cookwares - Chaosrimud, Duangkamol; Waluvanarak, Jitwilai; Roma, Jirapan; Phonhong, Nootjarin (Bulletin of Applied Sciences, 2022)
Determination of released cadmium, chromium, lead, molybdenum and nickel from stainless steel cookwares by ICP-OES was validated according to the analytical method of metals and alloys used in food contact materials and articles: a practical guide for manufacturers and regulators by ICP-OES. Results showed that linear range of cadmium was 0.05-1.0 mg/L while chromium, lead, molybdenum and nickel were 0.5-10 mg/L. The limit of detection of cadmium, chromium, lead, molybdenum and nickel were 0.4, 0.8, 3.3, 3.0 and 0.8 ug/L. The limit of quantitation of cadmium was 0.05 mg/L and the others were 0.5 mg/L.% Bias and intermediate precision showed that percentage recovery and relative pooled standard deviation of all elements were 97.8-118.4 and 0.95-6.36, respectively. Measurement uncertainty at 95% confident limit of all elements was less than 20%.